Principles for independent fiscal institutions and case studies - von Trapp, Lisa (OECD Publishing, 2016)
Independent fiscal institutions serve to promote sound fiscal policy and sustainable public finances. Today IFIs are considered among the most important innovations in the emerging architecture of public financial management. Within the OECD area, their number has more than tripled and is expected to continue to rise. This publication provides a unique set of in depth case studies of IFIs in 18 OECD member countries in light of many of the good practices for effective IFIs identified in the OECD Recommendation on Principles for Independent Fiscal Institutions
Keywords: Finance and Investment; Governance